Polyfunctional compound, composition, adhesive composition, adhesive composition set, adhesion method, and structure
A polyfunctional compound with flexible and rigid segments addresses the durability and reliability issues of structural adhesives by providing low temperature dependence of elongation rate, improving adhesion in diverse temperature environments.
Patent Information
- Application Number
- JP2022515400
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-17
- Filing Date
- 2021-04-13
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-04-13
AI Technical Summary
Structural adhesives used for bonding dissimilar materials face challenges with durability and reliability due to differences in thermal expansion coefficients, leading to stress and peeling issues, especially in applications requiring wide temperature ranges.
A polyfunctional compound with a balanced structure of flexible and rigid segments, arranged symmetrically within a molecule, is used to create an adhesive with low temperature dependence of elongation rate, comprising a polymer block with a polysiloxane skeleton and specific molecular weight distribution.
The adhesive exhibits reduced temperature dependence of elongation rate, enhancing durability and reliability across wide temperature ranges, suitable for bonding materials in automobiles, ships, and aerospace.
Smart Images

Figure 0007610588000019 
Figure 0007610588000001 
Figure 0007610588000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyfunctional compound, a composition, an adhesive composition, an adhesive composition set, an adhesion method, and a structure. [Background technology]
[0002] Structural adhesives are used in a wide variety of applications as highly reliable adhesives that can withstand heavy loads for long periods of time. Known types of structural adhesives include epoxy adhesives, urethane adhesives, and second generation (SGA) acrylic adhesives.
[0003] These structural adhesives have different properties depending on the type: for example, epoxy adhesives tend to have high adhesive strength and low elongation, urethane adhesives tend to have high elongation and low adhesive strength, and acrylic adhesives tend to have performance between epoxy adhesives and urethane adhesives.
[0004] Structural adhesives are used on a variety of substrates, including structural materials for automobiles and structural materials for ships and aerospace. Structural adhesives used on these substrates are required to bond different materials such as metals, resins, and glass. For example, aluminum and CFRP are used in some automobile components due to the demand for lighter components. These components are mainly joined by mechanical joining such as riveting, and structural adhesives such as epoxy-based adhesives used to join different materials are limited in the areas where they can be used.
[0005] This is because structural adhesives have problems with durability and reliability. Specifically, structural adhesives have poor extensibility after curing and cannot alleviate stress caused by the difference in linear expansion coefficients when joining different materials, resulting in durability deterioration and peeling of the adhesive surface (see, for example, Patent Documents 1 to 4).
[0006] For this reason, in order to alleviate the stress when different materials are joined, a one-part epoxy adhesive that uses an epoxy resin and a latent curing agent and has an elongation rate of 15% after curing has been proposed (see, for example, Patent Document 5). In addition, a curable resin composition that contains a urethane acrylate and a monofunctional unsaturated compound has been reported as a resin composition that has a high elastic modulus and elongation from low to high temperatures and has excellent water resistance and heat resistance (see, for example, Patent Document 6). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 4-145185 [Patent Document 2] Japanese Patent Application Publication No. 5-148337 [Patent Document 3] Japanese Patent Application Publication No. 5-156227 [Patent Document 4] Japanese Patent Application Publication No. 7-145225 [Patent Document 5] JP 2009-108278 A [Patent Document 6] Japanese Patent Application Publication No. 63-090525 Summary of the Invention [Problem to be solved by the invention]
[0008] As mentioned above, structural materials have different thermal expansion coefficients, so structural adhesives that bond dissimilar materials together must have not only adhesive strength for each dissimilar material, but also elongation. Furthermore, structural materials used in automobiles, ships, and aerospace applications must be able to withstand a wide range of temperatures, from low to high. Therefore, the adhesive strength and elongation of the structural adhesives that bond them together must remain constant over a wide range of temperatures, from low to high.
[0009] The present invention has been made in consideration of the above problems, and has an object to provide a polyfunctional compound capable of providing an adhesive having a low temperature dependency of elongation, as well as a composition, adhesive composition, adhesive composition set, bonding method, and structure each containing the polyfunctional compound. [Means for solving the problem]
[0010] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by using a polyfunctional compound having a structure in which a flexible chemical structure (soft segment) and a rigid chemical structure (hard segment) are arranged with high symmetry in one molecule, thereby completing the present invention.
[0011] That is, the present invention is as follows. [1] A polyfunctional compound represented by the following formula (1): [ka] (In the formula, X represents a carbon atom or a linking group having 1 to 20 carbon atoms and a valence of n, Ar represents an arylene group; R 1 each independently represents a divalent group containing a polymer block, R 2 each independently represents a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group, n represents an integer of 3 to 8. [2] The polymer block is a polymer block having at least one repeating unit selected from the group consisting of a siloxane bond unit, a urethane bond unit, an ether bond unit, a sulfide bond unit, a butadiene unit, and an isoprene unit. The polyfunctional compound according to [1]. [3] The polymer block has a polysiloxane skeleton. The polyfunctional compound according to [1] or [2]. [4] The glass transition temperature of the polymer block is 50° C. or less. The polyfunctional compound according to any one of [1] to [3]. [5] The polymer block has no melting point; The polyfunctional compound according to any one of [1] to [4]. [6] A plurality of the polyfunctional compounds having different n are included, The polyfunctional compound according to any one of [1] to [5]. [7] The number average molecular weight of the polyfunctional compound is 800 to 100,000. The polyfunctional compound according to any one of [1] to [6]. [8] The molecular weight distribution (Mw / Mn) of the polyfunctional compound is 1.5 or more. The polyfunctional compound according to any one of [1] to [7]. [9] The number average molecular weight of the polymer block is 200 to 20,000. The polyfunctional compound according to any one of [1] to [8].
[10] The Ar represents an arylene group having 6 to 10 carbon atoms. The polyfunctional compound according to any one of [1] to [9].
[11] The polyfunctional compound according to any one of [1] to
[10] , and a curing accelerator, composition.
[12] R 2 Further comprising a curing agent having a functional group that reacts with and forms a chemical bond with The composition described in
[11] .
[13] The composition according to
[11] or
[12] is included. Adhesive composition.
[14] A first agent containing the polyfunctional compound according to any one of [1] to
[10] ; and a second agent including a curing agent. Adhesive composition set.
[15] The method includes a step of adhering an adherend using the adhesive composition according to
[13] or the adhesive composition set according to
[14] . Adhesion method.
[16]
[13] or the adhesive composition set according to
[14] , structure. Effect of the Invention
[0012] According to the present invention, it is possible to provide a polyfunctional compound capable of providing an adhesive having a low temperature dependency of elongation, as well as a composition, adhesive composition, adhesive composition set, bonding method, and structure each containing the polyfunctional compound. [Brief description of the drawings]
[0013] [Figure 1] The NMR data of the compound obtained in Example 1 are shown below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Below, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail, but the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.
[0015] [Polyfunctional compound] The polyfunctional compound of the present embodiment is a compound represented by the following formula (1), and may be a mixture containing a plurality of compounds having different n in the following formula (1). [ka] (In the formula, X represents a carbon atom or a linking group having 1 to 20 carbon atoms and a valence of n, Ar represents an arylene group; R 1 each independently represents a divalent group containing a polymer block, R 2 each independently represents a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group, n represents an integer of 3 to 8.
[0016] The above polyfunctional compound has a structure in which polymer blocks extend from the linking group X via bulky arylene groups. The portion consisting of the linking group X and the arylene group Ar is a portion in which the bond rotation within the molecule is restricted by steric hindrance, and this portion is also called a hard segment. In contrast, R representing the polymer block 1 and a reactive group R 2 The portion constituted by the above is a portion that is not easily restricted by steric hindrance in the rotation of the bonds within the molecule, and this portion is also called a soft segment.
[0017] In this embodiment, n represents an integer of 3 to 8, and the polyfunctional compound has a 3- to 8-branched structure in which the arms of the soft segments extend around the hard segment. In this way, a compound having a flexible structure and a rigid structure with high symmetry in one molecule forms a uniform crosslinked structure when cured. In this uniform crosslinked structure, the molecular arrangement is regular and the stress distribution is reduced, so that the micro-Brownian motion is equally restricted and the property of low temperature dependency is considered to be exhibited. The reason for the low temperature dependency of the elongation is not limited to the above.
[0018] Therefore, the multifunctional compound of this embodiment is suitable for use as a structural adhesive for different materials used over a wide temperature range, such as adhesives for automobile structures and materials for ships and aerospace applications.
[0019] The n-valent linking group X having a carbon atom or 1 to 20 carbon atoms is not particularly limited, but examples thereof include the following saturated hydrocarbon groups having an n-branched structure, arene groups having an n-branched structure, saturated hydrocarbon groups having an n-branched structure in which a carbon atom is substituted with another atom such as oxygen, or groups in which a part of the branched chain of these groups is a substituent R x1Here, the terms "n-valent linking group" and "n-branched structure" mean that the linking group X has n soft segments. [ka] (In the formula, substituent R x1 is a group in which a hydrogen atom is a substituent R x2 represents a hydrocarbon group having 2 to 8 carbon atoms which may be substituted by
[0020] In the above example, the substituent R x1 However, the linking group X may have a branched structure having 3 to 8 substituents R x1 The substituent R x1 The hydrocarbon group having 2 to 8 carbon atoms represented by the formula (I) is not particularly limited, but examples thereof include linear, branched, or cyclic alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, pentyl, and cyclohexyl groups; and aryl groups such as phenyl and tolyl groups. x1 Substituent R that can be bonded to x2 Examples of the alkyl group include, but are not limited to, a halogen atom, a hydroxy group, an alkoxy group, a carbonyl group, an amino group, an imino group, a cyano group, and a thiol group.
[0021] The arylene group represented by Ar is not particularly limited, but examples thereof include a phenylene group and a naphthylene group. The arylene group Ar is a group in which a hydrogen atom is substituted with a substituent R ar The polyfunctional compound may be substituted with. Examples of such polyfunctional compounds include the following. Among these, an arylene group having 6 to 10 carbon atoms is more preferable, and a phenylene group is even more preferable. By using such an arylene group Ar, the rigidity of the hard segment tends to be further improved. [ka] (In the formula, R 1 ~R 2and n are as defined above, and the substituent R ar each independently represents a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms.
[0022] Substituent R ar The hydrocarbon group having 1 to 5 carbon atoms represented is not particularly limited, but examples thereof include linear, branched, or cyclic alkyl groups such as a methyl group, an ethyl group, a propyl group, an isopropyl group, and a butyl group.
[0023] R 1 represents a divalent group containing a polymer block. Such a polymer block is not particularly limited, but examples thereof include those having at least one repeating unit selected from the group consisting of a siloxane bond unit, a urethane bond unit, an ether bond unit, a sulfide bond unit, a butadiene unit, and an isoprene unit.
[0024] Examples of polymer blocks having these repeating units include a polysiloxane skeleton having a siloxane bond unit, a polyurethane skeleton having a urethane bond unit, a polyether skeleton having an ether bond unit, a polysulfide skeleton having a sulfide bond unit, a polybutadiene skeleton having a butadiene unit, and a polyisoprene skeleton having an isoprene unit. Among these, a polysiloxane skeleton having a siloxane bond unit is preferred. Such a R 1 By having such a structure, the flexibility of the soft segment tends to be further improved.
[0025] As described later, examples of the method for producing the polyfunctional compound of this embodiment include a method of reacting a polymer end with a polymerization coupling agent, and a method of polymerizing a monomer using a polyvalent initiator capable of generating multiple polymerization initiation ends. In such cases, the hard segment composed of the linking group X and the arylene group Ar can be said to be a portion derived from the polymerization coupling agent or the polyvalent initiator. In addition, R representing a polymer block 1 and a reactive group R 2The soft segment constituted by the above is a polymer or a polymerized portion of a monomer that is reacted with a polymerization coupling agent, and can be said to be a portion derived from a modified polymerization terminal as necessary.
[0026] From this point, R 1 The divalent group including a polymer block is a polymer block composed of repeating units and, as necessary, Ar or R at the end of the polymer block. 2 Also included are those having a connecting group for connecting to.
[0027] For example, assume that a polysiloxane skeleton, both ends of which are modified with epoxy groups, is used as the polymer block. In this case, R 1 The terminal on the Ar side of R has a connecting group formed by condensing a hydroxyl group or the like of a polymerization coupling agent with an epoxy group. 1 R 2 The terminal of the side has a connecting group derived from epoxy group modification, such as a methyl group portion of a glycidyl group. This is also true for a polyurethane skeleton having hydroxyl groups or carboxyl groups at both terminals and a polyether skeleton having hydroxyl groups at both terminals.
[0028] In addition, when a polybutadiene skeleton or a polyisoprene skeleton not having such functional groups at both ends is used as the polymer block, for example, polybutadiene or polyisoprene modified at both ends with hydroxyl groups or the like can be used. In this case, R 1 The terminal on the Ar side of R has a connecting group formed by condensing a hydroxyl group with a carboxyl group or the like of a polymerization coupling agent. 1 R 2 The terminal of the side is a hydroxyl group, for example, a glycidyl group (R 2 ) has a connecting group derived from the modification.
[0029] As mentioned above, R 1 The divalent group containing a polymer block is a group having Ar and R at its terminals. 2 The concept also includes the connecting groups for bonding to each of the above. Note that the above descriptions regarding the connecting groups are merely examples, and R1 The terminal of is not limited to the connecting group exemplified above. The number of atoms (excluding hydrogen atoms) constituting each connecting group is preferably 1 to 10, more preferably 1 to 5, from the viewpoint of functioning as a connecting group.
[0030] The glass transition temperature of the polymer block is preferably 50°C or lower, more preferably -150 to 25°C, even more preferably -150 to 0°C, still more preferably -150 to -10°C, even more preferably -150 to -50°C, and particularly preferably -150 to -75°C. When the glass transition temperature of the polymer block is 50°C or lower, the flexibility of the soft segment tends to be further improved. In addition, when the glass transition temperature of the polymer block is -150°C or higher, the hardness of the obtained cured product tends to be further improved. The glass transition temperature can be adjusted by the repeating units constituting the polymer block.
[0031] The polymer block preferably has no melting point. When the polymer block has no melting point, that is, when the polymer block is amorphous, the flexibility of the soft segment in the low temperature range tends to be improved. As an example of the amorphous polymer block, a polysiloxane skeleton having a siloxane bond unit can be mentioned. As an example of the polysiloxane skeleton, a polydimethylsiloxane skeleton can be mentioned.
[0032] The number average molecular weight of the polymer block is preferably 200 to 20,000, more preferably 300 to 10,000, and even more preferably 300 to 5,000. When the number average molecular weight of the polymer block is 300 or more, the length of the soft segments connecting the hard segments becomes longer when cured, and the stress distribution tends to be further reduced. When the number average molecular weight of the polymer block is 20,000 or less, the length of the soft segments connecting the hard segments becomes shorter when cured, and the hardness of the cured product tends to be further improved.
[0033] R2 represents a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group. Among these, a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, or an amino group is preferred, and a glycidyl group or a hydroxyl group is more preferred.
[0034] The weight-average molecular weight (Mw) of the polyfunctional compound is preferably 1500 to 250000, more preferably 4500 to 100000, and even more preferably 7000 to 450000. When the weight-average molecular weight of the polyfunctional compound is 1500 or more, the length of the soft segments connecting the hard segments becomes longer when cured, and the stress distribution tends to be further reduced. In addition, when the weight-average molecular weight of the polyfunctional compound is 250000 or less, the length of the soft segments connecting the hard segments becomes shorter when cured, and the hardness of the cured product tends to be further improved.
[0035] The number average molecular weight (Mn) of the polyfunctional compound is preferably 800 to 100,000, more preferably 1,000 to 80,000, even more preferably 2,000 to 50,000, and even more preferably 3,000 to 20,000. When the number average molecular weight of the polyfunctional compound is 800 or more, the length of the soft segments connecting the hard segments becomes longer when cured, and the stress distribution tends to be further reduced. In addition, when the number average molecular weight of the polyfunctional compound is 100,000 or less, the length of the soft segments connecting the hard segments becomes shorter when cured, and the hardness of the cured product tends to be further improved.
[0036] The molecular weight distribution (Mw / Mn) of the polyfunctional compound is preferably 1.5 or more, more preferably 1.5 to 4.0, and further preferably 2.0 to 3.5. When the molecular weight distribution of the polyfunctional compound is within the above range, the symmetry of the polyfunctional compound tends to be uniform overall.
[0037] In addition, the weight average molecular weight, number average molecular weight, and molecular weight distribution of a polyfunctional compound refer to the weight average molecular weight, number average molecular weight, and molecular weight distribution of the polyfunctional compound when the polyfunctional compound is a type of polyfunctional compound having a specific n value, and refer to the weight average molecular weight, number average molecular weight, and molecular weight distribution of the multiple polyfunctional compounds when the polyfunctional compound is a mixture of multiple compounds having different n values.
[0038] In this embodiment, the weight average molecular weight, number average molecular weight, and molecular weight distribution can be measured by gel permeation chromatography (GPC).
[0039] [Method for producing polyfunctional compounds] The method for producing the polyfunctional compound of the present embodiment is not particularly limited, but examples thereof include method A in which an end of a polymer is reacted with a polymerization coupling agent, and method B in which a monomer is polymerized using a polyvalent initiator capable of generating multiple polymerization initiation ends.
[0040] (Method A) Method A in which the terminal of a polymer is reacted with a polymerization coupling agent will be described. First, the raw materials used in the reaction will be described.
[0041] The polymerizable coupling agent is not particularly limited, but for example, a compound represented by the following formula (2) can be used. [ka] (In the formula, X represents a carbon atom or a linking group having 2 to 20 carbon atoms and a valence of n', each Ar represents an arylene group, and R 3 each independently represents a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group, and n' represents an integer of 3 to 10.
[0042] The linking group X and the arylene group Ar in the above formula (2) can be exemplified by the same groups as those exemplified for the above polyfunctional compound.
[0043] In addition, R in the above formula (2) 3 is the terminal group R of the polymer described below. 2' Examples of such groups include, but are not limited to, a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group.
[0044] In addition, n' in the above formula (2) can be the same value as or larger than the n exemplified in the above polyfunctional compound. This makes it easier to obtain a polyfunctional compound with n being 3 or more even if the reaction rate of the reaction between the polymeric coupling agent and the polymer is not 100%.
[0045] The polymer to be coupled with the polymerization coupling agent is not particularly limited, but for example, a polymer represented by the following formula (3) can be used. [ka] (In the formula, R 1' each independently represents a divalent polymer block; R 2' each independently represents a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group. 2' may be the same or different.)
[0046] R in the above formula (3) 1' Examples of the polymer block include the same ones as those exemplified for the polyfunctional compound. Specifically, the polymer block is not particularly limited, but examples thereof include those having at least one repeating unit selected from the group consisting of a siloxane bond unit, a urethane bond unit, an ether bond unit, a sulfide bond unit, a butadiene unit, and an isoprene unit.
[0047] In addition, R in the above formula (3) 2' is the polymer block R 1' is the terminal group of R 3The connecting functional group is not particularly limited, but examples thereof include a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, and an acid anhydride group.
[0048] In addition, R in the above formula (2) 3 and R in the above formula (3) 2' The functional groups may be appropriately selected from known combinations of functional groups capable of reacting with each other to form bonds, such as a hydroxyl group and an epoxy group, or a hydroxyl group and a carboxyl group.
[0049] Next, the reaction conditions are explained. Stoichiometrically, a polyfunctional compound having n soft segments can be obtained by reacting n moles of polymer with 1 mole of polymeric coupling agent. However, considering the actual reaction efficiency, the amount of polymer added with respect to 1 mole of polymeric coupling agent is preferably 1.0n to 1.5n moles. In addition, as described in formula (1), since a polyfunctional compound has three or more soft segments, the amount of polymer added with respect to 1 mole of polymeric coupling agent may be preferably 3.0 to 6.0 moles.
[0050] The reaction temperature, reaction time, and reaction atmosphere are determined by the R 3 and R in the above formula (3) 2' The reaction conditions are not particularly limited as long as they allow the reaction and the formation of a bond, and can be appropriately selected from known reaction conditions. As an example of the reaction conditions, the reaction can be performed at 100° C. for 24 hours under a nitrogen atmosphere, but the reaction conditions are not limited thereto.
[0051] By the above reaction, a compound represented by the following formula (4) can be obtained. [ka] (In the formula, X represents a carbon atom or a linking group having 1 to 20 carbon atoms and a valence of n, each Ar represents an arylene group, and R 1each independently represents a divalent group containing a polymer block; R 2' each independently represents a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group; and n represents an integer of 3 to 8.
[0052] The linking group X, the arylene group Ar, and the divalent group R in the above formula (4) 1 The R in the above formula (4) can be the same as those exemplified in the above polyfunctional compound. 2' is the polymer block R of the polymer used as the raw material 1' The terminal group is the same as that exemplified for the above polymer.
[0053] R in the above formula (4) 2' is the same as R in the above multifunctional compound. 2 or may be modified to any functional group to form R 2 The modification method is not particularly limited, and any conventionally known method can be used.
[0054] The polyfunctional compound obtained as described above may be one type of compound having a specific n value in formula (1), or may contain multiple compounds having different n values in formula (1). As the polyfunctional compound of the present embodiment, a compound containing one or multiple such polyfunctional compounds may be used as is, or a compound having a specific n value isolated from multiple polyfunctional compounds may be used.
[0055] In addition, the method for purifying a polyfunctional compound having a specific n independently is not particularly limited, but examples thereof include a method for separating the compounds based on differences in molecular weight using recycling gel permeation chromatography or the like.
[0056] (Method B) Next, a method B in which a monomer is polymerized using a polyvalent initiator capable of generating multiple polymerization initiation terminals will be described. The polyvalent initiator used in this method is not particularly limited, but for example, one having the same structure as the above-mentioned polymerization coupling agent and having a group R that functions as a polymerization initiator for anionic polymerization, cationic polymerization, living polymerization, etc. can be used.
[0057] The monomer is not particularly limited, but examples thereof include monomers capable of forming a siloxane bond unit, a urethane bond unit, an ether bond unit, a sulfide bond unit, a butadiene unit, and an isoprene unit.
[0058] [Composition] The composition of the present embodiment contains the above-mentioned polyfunctional compound and a curing accelerator, and optionally R 2 The composition may further contain a curing agent having a functional group that reacts with and forms a chemical bond. Such a composition has curability and can be suitably used as an adhesive composition described later. The use of the composition of the present embodiment is not particularly limited to adhesive use, and it can be used appropriately for other uses where curing properties are expected. The curing accelerator and the curing agent will be described below.
[0059] [Adhesive Composition] The adhesive composition of the present embodiment can be broadly divided into one-component adhesive compositions and two-component adhesive compositions. The one-component adhesive compositions can be further divided into homopolymerization adhesive compositions and curing agent reaction adhesive compositions. Each aspect will be described below.
[0060] (One-component type: homopolymerization type adhesive composition) The homopolymerization type adhesive composition of the present embodiment contains the above-mentioned polyfunctional compound and a curing accelerator. In this adhesive composition, the homopolymerization of the polyfunctional compound is accelerated by the curing accelerator, and the adhesive composition functions as an adhesive. More specifically, the curing accelerator is an R of the polyfunctional compound. 2By promoting bonding between the hard segments, the ends of the soft segments are bonded together, forming a cured product having a network-type molecular structure in which the hard segments serve as intersections and the soft segments connect to each other at their intersections.
[0061] As a hardening accelerator, R 2 There are no particular limitations on the R used as long as it promotes bonding between the R and 2 A known curing agent can be selected and used according to the requirements. 2 Examples of the curing accelerator when is an epoxy group include imidazole compounds such as 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 2-methylimidazole, 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, and 1-(2-cyanoethyl)-2-phenylimidazole; phosphorus compounds such as triphenylphosphine; tertiary amine compounds such as piperidine, dimethylpiperazine, triethylenediamine, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, 2,4,6,-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo[5.4.0]undec-7-ene; and organometallic compounds. The curing accelerator may be used alone or in combination of two or more. Among the curing accelerators, imidazole compounds are preferred. Among the imidazole compounds, one or more selected from the group consisting of 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole and 2-methylimidazole are preferred.
[0062] The content of the curing accelerator is preferably 0.1 to 20 parts by mass, preferably 0.3 to 10 parts by mass, and preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the polyfunctional compound. By having the content of the curing accelerator within the above range, the curability tends to be further improved.
[0063] (One-component type: hardener-reactive adhesive composition) The curing agent reaction type adhesive composition of this embodiment contains, in addition to the components described in the homopolymerization type adhesive composition, R 2The adhesive composition further contains a curing agent having a functional group that reacts with R of the multifunctional compound to form a chemical bond. In this adhesive composition, the curing accelerator accelerates the reaction between the multifunctional compound and the curing agent, and the adhesive composition functions as an adhesive. More specifically, the curing accelerator is a curing agent having a functional group that reacts with R of the multifunctional compound to form a chemical bond. 2 This promotes bonding between the functional groups of the hard segments and the curing agent residues, forming a cured product with a network-type molecular structure in which the soft segments connect the intersections of the hard segments and the curing agent residues.
[0064] The hardener is R 2 There are no particular limitations on the R used as long as it has a functional group that reacts with and forms a chemical bond. 2 A known curing agent can be selected and used according to the requirements. 2 When is an epoxy group, examples of the curing agent include bisphenols, biphenol, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 4,4,4-trihydroxytriphenylmethane, 1,1,1-tris(4-hydroxyphenyl)ethane, 4,4'-{1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene}bisphenol, α,α,α',α'-tetrakis(4-hydroxyphenyl)-p-xylene, 2,6-bis(dihydroxybenzyl)-4-methylphenol, 1,1,2,2-tetrakis(4- Examples of the curing agent include phenolic compounds such as hydroxy-3-methylphenyl)ethane, hydroquinone, resorcinol, naphthalenediol, phenol novolac resin, and cresol novolac resin; acid anhydride compounds such as methyltetrahydrophthalic anhydride, tetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride; aromatic amine compounds such as diaminodiphenylmethane and methylaniline; aliphatic amine compounds such as triethylenetetramine; and amine compounds such as isophoronediamine and methylcyclohexylamine. The curing agent may be used alone or in combination of two or more.
[0065] The content of the curing agent is preferably 0.1 to 100 parts by mass, more preferably 0.3 to 50 parts by mass, and more preferably 0.5 to 30 parts by mass, relative to 100 parts by mass of the polyfunctional compound. By having the content of the curing agent within the above range, the curability tends to be further improved.
[0066] In addition, the hardening accelerator is R 2 There are no particular limitations on the R to be used as long as it promotes the bonding of the R and the hardener. 2 Depending on the curing agent used, a known curing agent can be selected and used.
[0067] The ratio of the content of the curing agent to the content of the curing accelerator (content of the curing agent / content of the curing accelerator) is preferably 0.8 to 10, more preferably 1.0 to 7.5, and further preferably 1.2 to 5. When the ratio (content of the curing agent / content of the curing accelerator) is within the above range, the curability tends to be further improved.
[0068] (2-component adhesive composition set) The two-part adhesive composition set of this embodiment has a first part containing the above-mentioned polyfunctional compound and a second part containing a curing agent. 2 There are no particular limitations on the curing agent, and any known curing agent can be selected and used as long as it has a functional group that reacts with the compound to form a chemical bond. The first agent and / or the second agent may further contain a curing accelerator.
[0069] [Adhesion method] The adhesion method of the present embodiment includes a step of adhering an adherend using the one-component adhesive composition or two-component adhesive composition set. More specifically, a method of attaching a one-component adhesive composition or two-component adhesive composition set before curing to an adherend and curing it by heating can be mentioned. The adherend is not particularly limited, and examples thereof include different materials such as structural materials for automobiles and structural materials for ships and aerospace.
[0070] [Structure] The structure of the present embodiment is bonded using the one-component adhesive composition or the two-component adhesive composition set. The structure is not particularly limited, but examples thereof include structures in which different materials are bonded together, such as structural materials for automobiles, and structural materials for ships and aerospace. EXAMPLES
[0071] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0072] Example A1 44 g of 2-ethoxyethanol (Tokyo Chemical Industry Co., Ltd.) and 0.996 g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane (Tokyo Chemical Industry Co., Ltd.) were added to a 300 mL four-neck glass flask equipped with a Liebig condenser, a thermometer, a silicon rubber stopper for nitrogen replacement, and a glass stopper. A stirrer was then added to the four-neck flask, which was then placed on a magnetic stirrer with an oil bath. The mixture was stirred at 23°C for 30 minutes (stirring speed: 300 rpm) to completely dissolve the 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane.
[0073] 9.8 g of KF-105 (Shin-Etsu Chemical Co., Ltd., polydimethylsiloxane modified with glycidyl at both ends, epoxy equivalent 490 g / mol, number average molecular weight 980) and 0.108 g of Curesol TBZ (2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, Shikoku Chemical Industry Co., Ltd.) were added thereto, and the mixture was stirred at 23°C for 10 minutes (stirring speed: 300 rpm). Stirring was continued while nitrogen was poured in at a flow rate of 10 mL / min for 30 minutes. The nitrogen was stopped, and the mixture was stirred at 100°C for 24 hours (stirring speed: 300 rpm) to obtain a 2-ethoxyethanol solution containing the product.
[0074] The 2-ethoxyethanol solution containing the obtained product was subjected to solvent removal using an evaporator to obtain crude product 1. Next, crude product 1 was placed in a separatory funnel, 100 mL of ion-exchanged water was added, and the mixture was shaken well. The mixture was left to stand until the aqueous layer and the product were separated, and only the aqueous layer was removed. This was repeated three times to remove the reaction catalyst in the system, Curezol TBZ, and obtain product 1. The NMR of the obtained product 1 is shown in Figure 1. As a result, it was found that a mixture containing the following multifunctional compounds was obtained. The GPC data is shown in Table 1 below. [ka] (In the formula, R 1'' represents a structure having a polydimethylsiloxane skeleton.
[0075] Example A2 85 g of 2-ethoxyethanol and 0.996 g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane were added to a 300 mL four-neck glass flask equipped with a Liebig condenser, a thermometer, a silicon rubber stopper for nitrogen replacement, and a glass stopper. A stirrer was then added to the four-neck flask, which was then placed on a magnetic stirrer with an oil bath. The mixture was stirred at 23°C for 30 minutes (stirring speed: 300 rpm) to completely dissolve the 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane.
[0076] 20 g of X-22-163C (Shin-Etsu Chemical Co., Ltd., polydimethylsiloxane modified with glycidyl at both ends, epoxy equivalent 1000 g / mol, number average molecular weight 2000) and 0.210 g of Curesol TBZ (Shikoku Chemical Industry Co., Ltd.) were added thereto, and the mixture was stirred at 23°C for 10 minutes (stirring speed: 300 rpm). Stirring was continued while nitrogen was poured in at a flow rate of 10 mL / min for 30 minutes. The nitrogen was stopped, and the mixture was stirred at 100°C for 24 hours (stirring speed: 300 rpm) to obtain a 2-ethoxyethanol solution containing the product. Except for the above, the following product 2 was obtained in the same manner as in Example A1. The GPC data are shown in Table 1 below. [ka] (In the formula, R 1'' represents a structure having a polydimethylsiloxane skeleton.
[0077] Example A3 20 g of 2-ethoxyethanol and 0.996 g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane were added to a 300 mL four-neck glass flask equipped with a Liebig condenser, a thermometer, a silicon rubber stopper for nitrogen replacement, and a glass stopper. A stirrer was then added to the four-neck flask, which was then placed on a magnetic stirrer with an oil bath. The mixture was stirred at 23°C for 30 minutes (stirring speed: 300 rpm) to completely dissolve the 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane.
[0078] 4 g of X-22-163 (Shin-Etsu Chemical Co., Ltd., polydimethylsiloxane modified with glycidyl at both ends, epoxy equivalent 200 g / mol, number average molecular weight 400) and 0.050 g of Curesol TBZ were added thereto and stirred at 23°C for 10 minutes (stirring speed: 300 rpm). Stirring was continued while nitrogen was poured in at a flow rate of 10 mL / min for 30 minutes. The nitrogen was stopped and stirring was continued at 100°C for 24 hours (stirring speed: 300 rpm) to obtain a 2-ethoxyethanol solution containing the product. Except for the above, the following product 3 was obtained in the same manner as in Example A1. The GPC data are shown in Table 1 below. [ka] (In the formula, R 1'' represents a structure having a polydimethylsiloxane skeleton.
[0079] Example A4 The following product 4 was obtained in the same manner as in Example A1, except that 0.974 g of 4,4',4"-trihydroxytriphenylmethane (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of 0.996 g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane. The GPC data are shown in Table 1 below. [ka] (In the formula, R 1''represents a structure having a polydimethylsiloxane skeleton.
[0080] Example A5 The following product 5 was obtained in the same manner as in Example A1, except that 1.021 g of 1,1,1-tris(4-hydroxyphenyl)ethane (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of 0.996 g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane. The GPC data are shown in Table 1 below. [ka] (In the formula, R 1'' represents a structure having a polydimethylsiloxane skeleton.
[0081] Example A6 In a 300 mL four-neck glass flask equipped with a Liebig condenser, a thermometer, a silicon rubber stopper for nitrogen replacement, and a glass stopper, 45 g of 2-ethoxyethanol and 1.415 g of 4,4'-{1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene}bisphenol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added in place of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane. A stirrer was then added to the four-neck flask, which was then placed on a magnetic stirrer with an oil bath and stirred at 23°C for 30 minutes (stirring speed: 300 rpm) to completely dissolve 4,4'-{1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene}bisphenol.
[0082] 9.8 g of KF-105 and 0.112 g of Curesol TBZ (manufactured by Shikoku Chemical Industries) were added thereto, and the mixture was stirred at 23° C. for 10 minutes (stirring speed: 300 rpm). Stirring was continued while nitrogen was introduced at a flow rate of 10 mL / min for 30 minutes. The nitrogen was stopped, and the mixture was stirred at 100° C. for 24 hours (stirring speed: 300 rpm) to obtain a 2-ethoxyethanol solution containing the product. The following product 6 was obtained in the same manner as in Example A1, except for the above. The GPC data are shown in Table 1 below. [ka] (In the formula, R 1'' represents a structure having a polydimethylsiloxane skeleton.
[0083] [Example A7] 125 g of 2-ethoxyethanol and 1.557 g of tetrakis(glycidyloxyphenyl)ethane (GTR-1800, Nippon Kayaku Co., Ltd.) were added to a 300 mL four-neck glass flask equipped with a Liebig condenser, a thermometer, a silicon rubber stopper for nitrogen replacement, and a glass stopper. A stirrer was then added to the four-neck flask, which was then placed on a magnetic stirrer with an oil bath and stirred at 23°C for 30 minutes (stirring speed: 300 rpm) to completely dissolve the tetrakis(glycidyloxyphenyl)ethane.
[0084] 29.5 g of KF-2201 (Shin-Etsu Chemical Co., Ltd., polydimethylsiloxane modified with phenol at both ends, phenol equivalent: 1474 g / eq) and 0.311 g of Curesol TBZ were added thereto and stirred at 23°C for 10 minutes (stirring speed: 300 rpm). Stirring was continued while nitrogen was poured in at a flow rate of 10 mL / min for 30 minutes. The nitrogen was stopped and stirring was continued at 100°C for 24 hours (stirring speed: 300 rpm) to obtain a 2-ethoxyethanol solution containing the product. Except for the above, the following product 7 was obtained in the same manner as in Example A1. The GPC data are shown in Table 1 below. [ka] (In the formula, R 1'' represents a structure having a polydimethylsiloxane skeleton. 1'' also has a phenylene skeleton.
[0085] The products 1 to 7 are not limited to those having the above chemical formulas, but may include the compounds obtained from the reactions described in the respective examples, and may be separated and purified by known methods such as recycled GPC.
[0086] [GPC measurement conditions] 10 mg of the product obtained as described above was dissolved in 10 mL of tetrahydrofuran (stabilizer-free reagent grade, Fujifilm Wako Pure Chemical Industries, Ltd.), filtered through a membrane filter (PTFE, 0.50 μm), and subjected to gel permeation chromatography (GPC) analysis. The measurement conditions were as follows. Measuring device: D5280 LCS M-PDA (Shimadzu Corporation) Column: KF-801 (300mm x 8.0mm ID, Showa Denko) Column temperature: 40℃ Mobile phase: Tetrahydrofuran (stabilizer-free reagent grade, Fujifilm Wako Pure Chemical Industries, Ltd.) Flow rate: 1mL / min Detector: RI (Differential Refractive Index Detector) Standard material: Polystyrene Shodex STANDARD (Type: SL-105, Showa Denko)
[0087] [H 1 -NMR measurement conditions] The product obtained as described above was dissolved in deuterated chloroform (Tokyo Chemical Industry Co., Ltd., reagent grade) to prepare a 3% by mass solution, 1 H-nuclear magnetic resonance measurement ( 1 H-NMR was performed. Measuring device: AVANCE NEO (manufactured by BRUKER) Frequency: 500Hz Heavy solvent: Deuterated chloroform
[0088] [Table 1]
[0089] [Example B1] 5.40g of product 1 was mixed with 0.498g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 0.118g of Curezol TBZ, and 24.1g of 2-ethoxyethanol. The mixture was heated at 200°C for 2 hours to cure, resulting in a cured product. The evaluation results of the mixture are shown in Table 2.
[0090] Example B2 10.60g of product 2 was mixed with 0.498g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 0.222g of Curezol TBZ, and 45.3g of 2-ethoxyethanol. The mixture was heated at 200°C for 2 hours to cure, resulting in a cured product. The evaluation results of the mixture are shown in Table 2.
[0091] [Example B3] 2.50g of product 3 was mixed with 0.498g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 0.060g of Curezol TBZ, and 12.2g of 2-ethoxyethanol. The mixture was heated at 200°C for 2 hours to cure, resulting in a cured product. The evaluation results of the mixture are shown in Table 2.
[0092] [Example B4] 5.39 g of Product 4 was mixed with 0.487 g of 4,4',4"-trihydroxytriphenylmethane, 0.117 g of Curezol TBZ, and 24.0 g of 2-ethoxyethanol. The mixture was cured by heating at 200°C for 2 hours to obtain a cured product. The evaluation results of the mixture are shown in Table 2.
[0093] [Example B5] 5.41g of product 5 was mixed with 0.511g of 1,1,1-tris(4-hydroxyphenyl)ethane, 0.118g of Curezol TBZ, and 24.2g of 2-ethoxyethanol. The mixture was heated at 200°C for 2 hours to cure, resulting in a cured product. The evaluation results of the mixture are shown in Table 2.
[0094] [Example B6] 5.61g of product 6 was mixed with 0.708g of 4,4'-{1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene}bisphenol, 0.126g of Curesol TBZ, and 25.8g of 2-ethoxyethanol. The mixture was heated at 200°C for 2 hours to cure, and a cured product was obtained. The evaluation results of the mixture are shown in Table 2.
[0095] [Example B7] 15.53g of product 7 was mixed with 0.779g of tetrakis(glycidyloxyphenyl)ethane, 0.311g of Curezol TBZ, and 66.5g of 2-ethoxyethanol. The mixture was heated at 200°C for 2 hours to cure, resulting in a cured product. The evaluation results of the mixture are shown in Table 2.
[0096] [Example B8] 5.40g of Product 1, 0.520g of TD-2131 (phenol novolac resin manufactured by DIC, hydroxyl group equivalent: 104g / eq), 0.118g of Curesol TBZ, and 24.1g of 2-ethoxyethanol were mixed. The mixture was heated at 200°C for 2 hours to cure, and a cured product was obtained. The evaluation results of the mixture are shown in Table 2.
[0097] [Example B9] 10.00g of Product 1, 0.200g of Curesol 2MZ-H (2-methylimidazole, manufactured by Shikoku Chemical Industries), and 40.8g of 2-ethoxyethanol were mixed. The mixture was heated at 200°C for 2 hours to cure, and a cured product was obtained. The evaluation results of the mixture are shown in Table 2.
[0098] [Comparative Example B1] 1.89g of bisphenol A diglycidyl ether (jER828 manufactured by Mitsubishi Chemical Holdings, epoxy equivalent: 189g / eq), 1.016g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 0.058g of Curezol TBZ, and 11.9g of 2-ethoxyethanol were mixed. The resulting mixture was heated at 200°C for 2 hours to cure, yielding a cured product. The evaluation results of the resulting mixture are shown in Table 2.
[0099] [Comparative example B2] 9.80g of KF-105, 1.992g of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 0.108g of Curezol TBZ, and 44.0g of 2-ethoxyethanol were mixed. The mixture was heated at 200°C for 2 hours to cure, resulting in a cured product. The evaluation results of the mixture are shown in Table 2.
[0100] [Comparative Example B3] 11.24g of bisphenol F and 1,6-hexanediol glycidyl ether copolymer (Mitsubishi Chemical Holdings flexible epoxy resin YX7110, epoxy equivalent: 1124g / eq), 1.04g of TD-2131, 0.246g of Curesol TBZ, and 50.1g of 2-ethoxyethanol were mixed. The mixture was cured by heating at 200°C for 2 hours to obtain a cured product. The evaluation results of the mixture are shown in Table 2.
[0101] [Appearance of the cured product] The transparency of the cured product was visually observed.
[0102] [Tensile elongation] The test specimens were prepared according to JIS K 7161-1:2014 in an atmosphere of 23°C or -40°C, and the hardened specimens were shaped as 1BA dumbbell test specimens as specified in Annex A of JIS K 7161-1:2014. Tensile tests were performed using a universal testing machine, Instron model 3365 (manufactured by Instron), and the measured tensile strain was calculated in %.
[0103] [Glass transition temperature] A rectangular cured specimen with dimensions of 0.5 × 5 × 40 mm was used as a test piece. A dynamic viscoelasticity measuring device (DMS7100, manufactured by SII) was used to measure the temperature at a heating rate of 2°C / min, in the temperature range of -100 to 250°C, at a frequency of 1 Hz, and in tensile mode. The glass transition temperature (Tg) was calculated in °C from the peak top temperature of the loss tangent (tan δ) in the data.
[0104] [Table 2]
[0105] From the above results, it was found that by using the polyfunctional compound of Example 1, an adhesive with excellent flexibility was obtained, and the temperature dependency of the tensile breaking elongation was low, especially at temperatures around the glass transition temperature. In Comparative Examples B1 and B3, n in formula (1) was small at 2, and the temperature dependency of the tensile breaking elongation was high. In Comparative Example B2, n in formula (1) was small at 2, the appearance of the cured product was opaque, the curing was poor, and the tensile breaking elongation could not be measured. [Industrial Applicability]
[0106] The polyfunctional compound of the present invention has industrial applicability as a component of an adhesive.
Claims
1. A polyfunctional compound represented by the following formula (1): 【Chemistry 1】 ・・・ (1) (In the formula, X represents a linking group represented by any one of the following formulas: 【Chemistry 2】 Each of the substituents R x1 independently represents a hydrocarbon group having 2 to 8 carbon atoms; Ar represents an arylene group; R 1 each independently represents a divalent group having a number average molecular weight of 200 to 20,000 and including a polymer block having a polysiloxane skeleton, R 2 each independently represents a glycidyl group, a phenol group, a hydroxyl group, a carboxyl group, an amino group, a thiol group, a cyano group, a nitro group, or an acid anhydride group, n represents an integer of 3 to 8.
2. The glass transition temperature of the polymer block is 50° C. or less. The polyfunctional compound according to claim 1 .
3. The polymer block has no melting point; The polyfunctional compound according to claim 1 or 2.
4. A plurality of the polyfunctional compounds having different n are included. The polyfunctional compound according to any one of claims 1 to 3.
5. The number average molecular weight of the polyfunctional compound is 800 to 100,000. The polyfunctional compound according to any one of claims 1 to 4.
6. The molecular weight distribution (Mw / Mn) of the polyfunctional compound is 1.5 or more. The polyfunctional compound according to any one of claims 1 to 5.
7. The Ar represents an arylene group having 6 to 10 carbon atoms. The polyfunctional compound according to any one of claims 1 to 6.
8. The polyfunctional compound according to any one of claims 1 to 7, and a curing accelerator, composition.
9. The R 2 Further comprising a curing agent having a functional group that reacts with and forms a chemical bond with The composition of claim 8.
10. The composition according to claim 8 or 9, Adhesive composition.
11. A first agent containing the polyfunctional compound according to any one of claims 1 to 7; and a second agent including a curing agent. Adhesive composition set.
12. The method includes a step of adhering an adherend by using the adhesive composition according to claim 10 or the adhesive composition set according to claim 11. Adhesion method.
13. A laminate bonded using the adhesive composition according to claim 10 or the adhesive composition set according to claim 11. structure.
Citation Information
Patent Citations
Curable resin composition
JP1988090525A
Structural adhesive
JP1992145185A
Epoxy resin composition suitable for structural adhesive
JP1993148337A
Structural adhesive
JP1993156227A
Bonding epoxy resin composition
JP1995145225A